Computing stable epimorphisms onto finite groups. (May 2019) - Požar, Rok
Abstract: Let U be a finitely presented group with a normal subgroup F, and let H be a finite group. We present an effective method for constructing all U -stable epimorphisms from F onto H ; that is, epimorphisms whose kernels are normal in U . Our strategy is an adaptation of the algorithm for determining all epimorphisms from a finitely presented group onto a finite group. As an application, we construct all admissible regular graph covering projections with a given deck transformation group.